A Novel Approach for Treatment of an Unusual Presentation of Radicular Cysts Using Autologous Periosteum and Platelet-Rich Fibrin in Combination with Demineralized Freeze-Dried Bone Allograft - Veena A. Patil; Manthan H. Desai; Veerendra S. Patil; Hanisha Reddy Kaveti; Kiran Kumar Ganji; Prasanna M. Danappanavar (Hindawi Limited, 2013)
Radicular cysts are the most common cystic lesions affecting the jaws. They are most commonly found at the apices of the involved teeth. This condition is usually asymptomatic but can result in a slow-growth tumefaction in the affected region. The following case report presents the successful treatment of radicular cysts using autologous periosteum and platelet-rich fibrin with demineralized freeze-dried bone allograft.